Enrichment of Autotrophic Denitrifiers From Anaerobic Sludge Using Sulfurous Electron Donors - Carboni, M. F.; Florentino, A. P.; Costa, R. B.; Zhan, X.; Lens, P. N. L. (Frontiers in Microbiology, 2021)
This study compared the rates and microbial community development in batch bioassays on autotrophic denitrification using elemental sulfur (S0), pyrite (FeS2), thiosulfate (S2O32-) and sulfide (S2-) as electron donor. The performance of two inocula was compared: digested sludge (DS) from a wastewater treatment plant of a dairy industry and anaerobic granular sludge (GS) from a UASB reactor treating dairy wastewater. All electron donors supported the development of a microbial community with predominance of autotrophic denitrifiers during the enrichments, except for sulfide. For the first time, pyrite revealed to be a suitable substrate for the growth of autotrophic denitrifiers developing a microbial community with predominance of the genera Thiobacillus, Thioprofundum and Ignavibacterium. Thiosulfate gave the highest denitrification rates removing 10.94 mM NO3- d-1 and 8.98 mM NO3- d-1 by DS and GS, respectively. This was 1.5 and 6 times faster than elemental sulfur and pyrite, respectively. Despite the highest denitrification rates were observed in thiosulfate-fed enrichments, an evaluation of the most relevant parameters for a technological application revealed elemental sulfur as the best electron donor for autotrophic denitrification with a total cost of 0.38 € per m3 of wastewater treated.